The use of language learning strategies in a second and third language: The case of foreign language majors - Pawlak, Mirosław; Kiermasz, Zuzanna (Studies in Second Language Learning and Teaching, 2018)
Although multilingualism has become a fact of life in the last few decades, this phenomenon has largely failed to find a reflection in research on language learning strategies. Even when scholars have addressed this issue, it has mostly been done with the purpose of proving the advantage of multilingualism over bilingualism, and scant attention has been given to how the nature, utility or status of a particular additional language can impact the frequency and patterns of strategy use. The present paper seeks to partially fill this gap by investigating the employment of strategies by 107 Polish university students majoring in English and, at the same time, being required to reach a high level of proficiency in another additional language. The data were collected by means of the Strategy Inventory for Language Learning (Oxford, 1990) and interviews conducted with selected participants. A combination of quantitative and qualitative analysis demonstrated that strategy use in the second language was higher than in the third language, both overall and with respect to specific groups of strategies, mostly traditional and memory strategies were deployed, and the outcomes could be attributed to the proficiency level in both languages and varied motivation to master these languages.